Application Of Nanotechnology Using Steel Fiber Reinforced Concrete With Stone Dust For Developing Sustainable Building Materials - Abdul Ghaffar Noor Mohd; Divya Prakash (Elementary Education Online, 2023)
Nowadays due to urbanization and industrialization, global warming is reaching an alarming level and provides adverse effects on human life as well as on climate. It’s right and high time to design and develop a sustainable solution to address the serious issue. This study investigated Nano modification in the design of concrete under huge realization in the construction world. The age of concrete in the construction industry can be increased by improving the strength of concrete by utilizing the byproducts and construction waste industry because of sustainable development of building construction material and environmental protection. This is a positive step as the life of the structure is increased by using sustainable materials. Nano materials like nano-alumina, carbon nanotubes, titanium oxide, nano alumina, etc. This study reported the influence of nano-silica on mechanical properties such as compressive strength, of M35 grades of concrete with the use of optimized nano-silica as a partial replacement of cement. The experimental results were compared both with and without nano-silica in SFRC; it was found that the mechanical properties of concrete can be enhanced by nano-silica with SFRC. The design concrete is nano-silica steel fiber reinforced concrete (NSSFRC). In this research work, both hooked ends fibers are used to find the mechanical properties of concrete, with a fiber length of 60mm and diameters of 0.75 mm with a 0.45 w/c ratio. Addition of steel fibers with volume fractions, 0.5%, 1.0%, and 1.5% and nano-silica added with different volume fractions 7.5 %, 15%, and 20% by weight of cement. Twenty-seven concrete mixes were considered for this experimentation and investigated the influenced properties of concrete. Also studied the area variation as in the case of different volume fractions of fibers. The experimental results show that the tilt towards the positive side with the addition of fiber with nano silica resulting an increase in mechanical properties of future concrete by 12-30% in compressive strength